2004
DOI: 10.1002/qua.20246
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the structure and properties of uric acid: A potent antioxidant

Abstract: ABSTRACT:A detailed study of tautomeric properties of uric acid, its different anions, and radical species was performed at the DFT level, employing B3LYP functional and the 6-311ϩϩG(d,p) basis set. Single-point energy calculations were also performed at the MP2 level using B3LYP/6-311ϩϩG(d,p) optimized geometries and the cc-pVTZ and 6-311ϩϩG(d,p) basis sets. The effect of aqueous solvation on the relative stability of the neutral and anionic species was investigated using Tomasi's polarized continuum model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
6
9
0
1
Order By: Relevance
“…Our calculations using B3LYP/6‐31+G** and MP2//B3LYP/6‐31+G** methods give a vertical IP for uric acid of 192.3 and 199.0 kcal/mol, respectively. This is consistent with experiment by Dougherty et al 21 and with calculations reported by Allen et al 6, who report values of 192.8 kcal/mol using B3LYP/6‐311++G** and of 200.9 kcal/mol using MP2//B3LYP/6‐311++G**.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our calculations using B3LYP/6‐31+G** and MP2//B3LYP/6‐31+G** methods give a vertical IP for uric acid of 192.3 and 199.0 kcal/mol, respectively. This is consistent with experiment by Dougherty et al 21 and with calculations reported by Allen et al 6, who report values of 192.8 kcal/mol using B3LYP/6‐311++G** and of 200.9 kcal/mol using MP2//B3LYP/6‐311++G**.…”
Section: Resultssupporting
confidence: 92%
“…According to all methods employed, the most stable form is the triketo structure U0A. This is in agreement with results reported by Demir et al 5 at the semiempirical level, by Chen et al 4 both at the semiempirical level and at a rather low ab initio level, and by Allen et al 6 at a higher DFT level. This is also consistent with crystallographic study by Ringertz 14 in which uric acid in its crystalline form was found to exist in a planar triketo structure.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The optimized bond lengths of uric acid H 2 U we obtained from B3LYP/6-311+G(d,p) are compared with previous studies [29][30][31] in Table 1, together with those of H 2 U, HU − , and U 2− in aqueous solution. Many of the changes in bond lengths of the anions can be rationalized in terms of resonance, such as the lengthening of C4-C5 and the three C-O bonds, as well as the shortening of C2-N3, N3-C4, C5-C6, and C8-N9 in urate(aq).…”
Section: Resultsmentioning
confidence: 96%
“…L'acide urique est le produit catabolique final des purines chez l'humain et peut assumer un rôle d'antioxydant hydrosoluble (Allen et al, 2004;Chamorro et al, 2004;Reeshemah et al, 2004). On le retrouve dans le sang à des concentrations nettement plus élevées que celle des autres antioxydants (Chamorro et al, 2004).…”
Section: Liste Des Tableauxunclassified